Freies Rheinland : Fest im Griff und aus der Reihe. (Köln : Face to Face, 1989)
Bakos, Andrea ; Cieslik, Lisa ; Hawk, Tom A. ; De Heart, Shahin ; Hombreg, Karl-Heinz ; Inda ; Jäger, Ruth ; etc.
Freies Rheinland : Fest im Griff und aus der Reihe, Face to Face, Köln, 1989
boek